Transformational leadership in action: A case study on the role of NGOs in reducing poverty and catalyzing social change in Egypt. - El Akkad, Nour (AUC Knowledge Fountain, 2016)
This study presents the concept of transformational leadership and suggests that non-governmental organizations (NGOs), as transformational leading agencies, have a vital role in addressing community needs in Egypt. The study is conducted using the qualitative research method, focusing on the case study of Alashanek Ya Balady Association for Sustainable Development (AYB-SD), which is an Egyptian NGO directing its efforts towards poverty alleviation and social change in the district of Old Cairo in Cairo. The study inspects the different programs of the NGO using the SWOC (Strengths, Weaknesses, Opportunities and Challenges) approach that examines the internal and external environments in which the NGO operates. Moreover, throughout the study, reference is made to the efforts of the state, or lack thereof, in supporting the work of NGOs in Egypt. Finally, the study concludes by providing recommendations for the government as well as the NGOs, which can enhance their work and, hopefully, help them in paving the road to a more developed Egypt.